Specific inhibition of secreted NRG1 types I–II by heparin enhances Schwann Cell myelination. Issue 7 (3rd May 2016) - Eshed‐Eisenbach, Yael; Gordon, Aaron; Sukhanov, Natalya; Peles, Elior
Abstract : Primary cultures of mixed neuron and Schwann cells prepared from dorsal root ganglia (DRG) are extensively used as a model to study myelination. These dissociated DRG cultures have the particular advantage of bypassing the difficulty in purifying mouse Schwann cells, which is often required when using mutant mice. However, the drawback of this experimental system is that it yields low amounts of myelin. Here we report a simple and efficient method to enhance myelination in vitro . We show that the addition of heparin or low molecular weight heparin to mixed DRG cultures markedly increases Schwann cells myelination. The myelin promoting activity of heparin results from specific inhibition of the soluble immunoglobulin (Ig)‐containing isoforms of neuregulin 1 (i.e., NRG1 types I and II) that negatively regulates myelination. Heparin supplement provides a robust and reproducible method to increase myelination in a simple and commonly used culture system. GLIA 2016;64:1227–1234 Main Points: Heparin enhances myelination by mouse Schwann cells in vitro . Heparin inhibits NRG1 type I and II, which negatively regulate myelination. Describes a simple and efficient method to increase Schwann cell myelination.